2012
DOI: 10.1016/j.seizure.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

8p deletion and 9p duplication in two children with electrical status epilepticus in sleep syndrome

Abstract: We describe two individuals with the same chromosomal aberrations derived from an unbalanced translocation between chromosomes 8p and 9p, who presented with intellectual disabilities, dysmorphic features, and localization-related epilepsy. Several years after the onset of epilepsy, aggravation of widespread epileptic discharges during sleep resulted in the emergence of absence and/or atonic seizures in both patients; one patient additionally presented with psychomotor deterioration. These symptoms completely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… Unknown Dup 0.8–9.2 Mb. Unknown 5 Microduplication syndrome Unknown Unknown Giorda R et al 2009 [ 53 ] 16p13 Chr16:10,246,239–10,354,862 Del 109Kb 1 GRIN2A 4 ESESS/CSWSS > 50% Channelopathy Lesca et al, 2012 [ 12 ], Constanze Reutlinger et al 2010 [ 54 ] 8p23.3 Unknown Del 1.8-Mb 3 FBXO25 2 8p deletion syndrome 20–30% Unknown Tojo Nakayama et al 2012 [ 55 ] 9p24.2 Unknown Dup 2.6-Mb Unknown 2 9p duplication syndrome 50–60% Unknown Tojo Nakayama et al 2012 [ 55 ] 14q21.3 Chr14:47,592,578–47,662,394 Del 70Kb 1 MDGA2 1 ESESS/CSWSS > 50% Metabolism of proteins Lesca et al 2012 [ 12 ] 22q13.32-q13.33 Chr22:49,346,697–51,219,009 Del 1.9 Mb 45 SHANK3 1 ESESS/CSWSS > 50% Synapse connection Lesca et al 2012 [ 12 ] 16q23.3 Chr16:83,599,498–83,857,382 Del 258Kb 2 CDH13 1 ESESS/CSWSS > 50% Cell adhesion Lesca et al 2012 [ 12 ] ...…”
Section: Resultsmentioning
confidence: 99%
“… Unknown Dup 0.8–9.2 Mb. Unknown 5 Microduplication syndrome Unknown Unknown Giorda R et al 2009 [ 53 ] 16p13 Chr16:10,246,239–10,354,862 Del 109Kb 1 GRIN2A 4 ESESS/CSWSS > 50% Channelopathy Lesca et al, 2012 [ 12 ], Constanze Reutlinger et al 2010 [ 54 ] 8p23.3 Unknown Del 1.8-Mb 3 FBXO25 2 8p deletion syndrome 20–30% Unknown Tojo Nakayama et al 2012 [ 55 ] 9p24.2 Unknown Dup 2.6-Mb Unknown 2 9p duplication syndrome 50–60% Unknown Tojo Nakayama et al 2012 [ 55 ] 14q21.3 Chr14:47,592,578–47,662,394 Del 70Kb 1 MDGA2 1 ESESS/CSWSS > 50% Metabolism of proteins Lesca et al 2012 [ 12 ] 22q13.32-q13.33 Chr22:49,346,697–51,219,009 Del 1.9 Mb 45 SHANK3 1 ESESS/CSWSS > 50% Synapse connection Lesca et al 2012 [ 12 ] 16q23.3 Chr16:83,599,498–83,857,382 Del 258Kb 2 CDH13 1 ESESS/CSWSS > 50% Cell adhesion Lesca et al 2012 [ 12 ] ...…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in patient 5, seizures may be linked to trisomy 9p. This trisomy is associated with cerebral, neurological, and epileptic abnormalities (Nakayama et al, 2012;Stern, 1996). Array revealed that patient 2 presented a small deletion located at 17q21.3.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic data were collected from the literature where approximate breakpoints are known for 53 individuals with 9p deletion and duplication syndromes. 12 , 14 , 15 , 16 , 17 , 19 , 27 , 29 , 30 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 …”
Section: Methodsmentioning
confidence: 99%